Analisis Kecenderungan Kecelakaan Kapal Di Indonesia - Malisan, Johny (Warta Penelitian Perhubungan, 2010)
Ship accident is important to be considered in the view of its tend to increase. Shipping safety thereforeshould be a main factor because function of sea transportation as a goods and human mobilities,distrubution of development, nation unihj, and supporting of national economy. This assesment isfocused on statistical analysis on the increase of ship accident in order to augment safety of seatransportation. Human factors dominating cause of the accident (i.e 42.08%) then followed by natureand technical factors respectively 32.99 % and 24.92 %. Those percentages give an indication of atendency for not complying to safety regulation and often do not pay attention to safety equipments.Human resources aspect is dominant that in this assessment comprehensive efforts needed to preventship accidents. Other efforts are safety standard requirements toward aspects of infra andsupra structures of sea transportation for realising effective and efficient sea transportationservices.Key word : ship acci.dents, age of fleet, human resources, and regulations